2017
DOI: 10.1007/s00421-017-3746-2
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant external pneumatic compression treatment with consecutive days of high intensity interval training reduces markers of proteolysis

Abstract: EPC when used concurrently with HIIT and in subsequent recovery days reduces skeletal muscle markers of proteolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 35 publications
0
23
0
1
Order By: Relevance
“…It is consistent with the present study, where VAS showed a sharp increase in the first 24 h and a very mild increase after 48 h in all groups. There was no difference in VAS increase with INP or IPC after 24 or 48 h. Most previous research yielded no statistically significant results, with no differences after applying IPC [ 24 , 26 , 27 ]. Fonda et al (2015) described an improvement in VAS after INP, while van Rensburg et al (2017) found no difference, similar to the present study [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…It is consistent with the present study, where VAS showed a sharp increase in the first 24 h and a very mild increase after 48 h in all groups. There was no difference in VAS increase with INP or IPC after 24 or 48 h. Most previous research yielded no statistically significant results, with no differences after applying IPC [ 24 , 26 , 27 ]. Fonda et al (2015) described an improvement in VAS after INP, while van Rensburg et al (2017) found no difference, similar to the present study [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 71%
“…No difference was observed between groups. Most previous research also identified no difference in CK levels using compression [ 23 , 24 ] or negative pressure [ 12 , 13 ]. A recent study demonstrated a more significant CK decrease after INP than after active recovery therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study included strength-trained males [26]. Two studies included physically active volunteers [30] [18] and athletes [31] [32], another two studies chose healthy participants [19] [27]. Detailed information about the training status is presented in the Table 1.…”
Section: Details Of the Intervention Groups In The Included Studiesmentioning
confidence: 99%